Molecular Diagnosis and Identification of Equine Piroplasms: Challenges and Insights from a Study in Northern Italy - Veronica Facile; Martina Magliocca; Filippo Maria Dini; Ilaria Imposimato; Jole Mariella; Francesca Freccero; Lorenza Urbani; Riccardo Rinnovati; Emily Sel; Laura Gallina; Carolina Castagnetti; Roberta Galuppi; et al. (Animals)
Equine piroplasmosis is a tick-borne disease caused by Babesia and Theileria species. Despite its presence in Europe, no laboratory testing is required for animal movement, even though some countries remain free of this disease. Differentiating between species and genotypes is crucial to determine the most effective treatment, as dosage, active compounds, and duration vary. However, diagnosis is often challenging due to genetic variability and the limited sensitivity of molecular methods. The aims of this study were to compare the performances of different molecular diagnostic tests to identify the most effective assay for piroplasm DNA detection and to genetically characterize the piroplasms identified in horses in Northern Italy from 2016 to 2022. Among 63 horses tested, 24 (38.1%) were positive in at least one of the tests used. Four horses tested positive for Babesia caballi with identical nucleotide sequences, while 22 horses tested positive for genetically different Theileria species, including Theileria equi, Theileria haneyi-like species, and Theileria sp. Africa. Two horses were coinfected by Babesia caballi and Theileria haneyi-like species. The best diagnostic approach to avoid false negative results was a combination of different assays. Further studies will be necessary to better assess the prevalence and genetic diversity of piroplasms involved in equine piroplasmosis.